COMPARATIVE STUDY OF TOTAL LIPIDS IN THE MUSCLES OF CYPRINUS CARPIO REARING IN PONDS AND RIVER - Karim, Y. A.; Al-Rudainy, A. J.; Abbas , L .M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of the current study is to compare total lipid profile of Cyprinus carpio reared in earthen ponds and wild fish (river). A total of 80 fish samples were collected from these  locations for the period from November-December 2020 and divided into three weight groups ( W1 , less than 500 g ;W2, 500-1000g  and W3 , more than 1000g). Results of present study showed that the total cholesterol content ranged between 17.69-21.63mg\100g in W3 and W1 respectively in river fish, while in pond fish ranged between 22.08-23.59mg\g in W2 and W3 respectively. High density lipoprotein in river fish ranged between 5.84-12.21mg\g in W3 and W1 respectively, in pond fish ranged between 11.18-12.92mg\g in W2 and W1. Low density lipoprotein in river fish ranged between 0.908-1.215 mg\g in W3 and W2, in pond fish ranged between 1.266-1.588 mg\g in W2 and W3 respectively and finally triglycerides in river fish ranged between 53.25-59.69 mg\g in W3 and W1.In pond fish ranged between 60.57-65.98 mg\g in W2 and W3 respectively. Results of statistical analysis of  lipid profile showed  a significant difference P≤0.05 of Cholesterol, HDL,LDL and Triglycerides in W3 between ponds and river fish , but no significant difference P>0.05 in W1 and W2 of Cholesterol, HDL,LDL and Triglycerides between ponds and river fish.